DNA repair genetic polymorphisms and risk of colorectal cancer in the Czech Republic - Pardini, B; Naccarati, A; Novotny, J; Smerhovsky, Z; Vodickova, L; Polakova, V; Hanova, M; Slyskova, J; Tulupova, E; Kumar, R; Bortlik, M; Barale, R; et al. (Mutation research, 2008)
Colorectal cancer represents a complex disease where susceptibility may be influenced by genetic polymorphisms in the DNA repair system. In the present study we investigated the role of nine single nucleotide polymorphisms in eight DNA repair genes on the risk of colorectal cancer in a hospital-based case-control population (532 cases and 532 sex- and age-matched controls). Data analysis showed that the variant allele homozygotes for the Asn148Glu polymorphism in the APE1 gene were at a statistically non-significant increased risk of colorectal cancer. The risk was more pronounced for colon cancer (odds ratio, OR: 1.50; 95% confidence interval, CI: 1.01-2.22; p=0.05). The data stratification showed increased risk of colorectal cancer in the age group 64-86 years in both individuals heterozygous (OR: 1.79; 95% CI: 1.04-3.07; p=0.04) and homozygous (OR: 2.57; 95% CI: 1.30-5.06; p=0.007) for the variant allele of the APE1 Asn148Glu polymorphism. Smokers homozygous for the variant allele of the hOGG1 Ser326Cys polymorphism showed increased risk of colorectal cancer (OR: 4.17; 95% CI: 1.17-15.54; p=0.03). The analysis of binary genotype combinations showed increased colorectal cancer risk in individuals simultaneously homozygous for the variant alleles of APE1 Asn148Glu and hOGG1 Ser326Cys (OR: 6.37; 95% CI: 1.40-29.02; p=0.02). Considering the subtle effect of the DNA repair polymorphisms on the risk of colorectal cancer, exploration of gene-gene and gene-environmental interactions with a large sample size with sufficient statistical power are recommended.
Keywords: Male; Smoking; lidé středního věku; kouření; studie případů a kontrol; senioři nad 80 let; genotyp; Aged, 80 and over; Age Factors; Humans; Middle Aged; rizikové faktory; senioři; Czech Republic; Česká republika; kolorektální nádory; mužské pohlaví; oprava DNA; Female; Aged; Case-Control Studies; DNA Repair; ženské pohlaví; Polymorphism, Single Nucleotide; Genetic Predisposition to Disease; věkové faktory; jednonukleotidový polymorfismus; Colorectal Neoplasms; Adult; Risk; riziko; genetická predispozice k nemoci; dospělí; lidé; Genotype; Risk Factors